14 February: Transfiguration - Knowles, Michael P. (The expository times, 2010)
The author reflects on the essence of the Feast of the Transfiguration. He describes the reaction of the three disciples chosen by Jesus Christ to take with Him to pray on a mountain when they saw His transfiguration. In the author's view, the Transfiguration offers a look of glory amidst the suffering in life for disciples of every age and every level of understanding. He adds that Christians come to the Transfiguration of Christ to be illuminated and transformed by it.